TINJAUAN YURIDIS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCURIAN DENGAN KEKERASAN (Studi Putusan Nomor 164/Pid.B/2023/PN Kla) - Prasetyo, Wawan; Prasetyawati, Endang; Alfiyan, Angga (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
This study aims to analyze law enforcement regarding the causal factors and considerations of judges in cases of violent theft. The sources and types of data used are primary and secondary data. Data collection through library research and field research. The causal factors for violent theft include; Family factors, family disturbances, mental stress, and damaged values can drive someone towards deviant behavior. Then the judge has considered several things, namely: Proof based on valid evidence as regulated in Article 184 paragraph (1) of the Criminal Procedure Code, which includes: witness statements, evidence and statements from the defendant, in court have been proven legally and convincingly. Keywords: Law enforcement; Criminal act; Theft; Violence